Obex [videorecording (DVD)] - Birney, Albert; Birney, Albert; Ohs, Pete; Hernandez, Callie, 1988-; Mosley, Frank (Oscilloscope Laboratories, 2026)
Conor Marsh's secluded life is disrupted when he plays the OBEX game. His dog Sandy disappears, blurring reality and game. Conor enters the OBEX world to rescue Sandy, navigating its strange realms.